The Role of Yonzipur 9/LLB/1 Kostrad in the Earthquake Emergency Response Phase (Case Study of Earthquake Disaster in Cianjur) - Baihaqi, Lukman Hakim; Kurniadi, Anwar (Ridwan Institute, 2023)
Indonesia is a country that has a very high level of vulnerability disasters it can occur anytime and anywhere. Based on this situation, Yonzipur 9/LLB as a unit of the Indonesian Army which is part of the Rapid Response Team for Disaster Management (PRCPB) has a very important role in providing assistance to the government and the community in dealing with natural disasters, especially during the emergency response phase. Preparedness and maintenance of Yonzipur 9/LLB capabilities play a key role in ensuring the success of emergency response operations. In this journal, the author examines the role of Yonzipur 9/LLB in the emergency response period for the earthquake that occurred in Cianjur on November 21, 2022 using a quantitative method. Data collection was obtained through observation, interviews and literature study. The role of the TNI in handling the earthquake disaster in Ciancur cannot be separated from the duties and functions of the TNI which have been mandated in Law Number 34 of 2004. Yonzipur 9/LLB has taken strategic and responsive steps in the framework of the earthquake disaster emergency response operation accompanied by coordination and good cooperation with local government and other agencies.